A Review on Carbon Nanotubes: Preparation, Properties and Applications - Karim, Md Nur; Patwary, M.A. Sayed; Abedin, S.M. Ashik; Hossen, Md Riaj; Rahman, Md Saifur (Journal of Research Updates in Polymer Science, 2020)
Carbon nanotubes(CNTs) have achieved attention in recent times because of their extraordinary physicochemical properties like strength, flexibility, sensors, conducting etc. Carbon nanotubes(CNTs) are known as nano-architectured allotropes of carbon, having graphene sheets which are rolled up into cylinder that forms carbon nanotubes. In the field of nanotechnology, carbon nanotubes are the one of the most unique invention. The eye-catching features of carbon nanotubes are their electronic, mechanical, optical and chemical characteristics, which open a way to future applications. Carbon nanotubes can be single walled and multi walled which can be produced in various ways. The most common techniques used nowadays are: arc discharge, laser ablation and chemical vapour deposition. In this review article,the applications of CNTs in various technologically important fields are discussed in detail.